Poznanie języka jako fundament pracy misyjnej. Prace ojców białych nad gramatyką języka bemba - Madej, Małgorzata (Annales Missiologici Posnanienses, 2021)
It was always important for the Church, that a communication between the preacher and the listener was the best; the former must be understood in such a way that the latter is moved by the words of the Gospel. Before the arrival of Europeans in Central Africa (in late nineteenth century), the Bemba people did not know any written form, and their language only had a spoken form. It was with the arrival of Europeans on the Bemba lands that the era of learning, writing, studying and classifying the language of this ethnic group began. The first Europeans to reach the Bemba area were the missionaries, the White Fathers, and it was they who, after beginning their missionary activity, began to study the Bemba language. This article presents the achievements of the White Fathers in this field and tries to explain how the process of learning the Bemba language by the White Fathers was carried out.